Understanding the war in Kosovo - Bieber, Florian; Daskalovski, Židas (Frank Cass, 2003)
The war in Kosovo has been a defining moment in post-Cold War Europe. Kosovo has great importance beyond the Balkans as the most ambitious attempt of the international community to prevent internal conflicts and rebuild a society destroyed by war and ethnic cleansing. As the danger of ethnic conflict prevails in the region and elsewhere around the world, the experience of Kosovo offers important lessons. This is a comprehensive survey of developments in Kosovo leading up to, during and after the war in 1999, providing additionally the international and regional framework to the conflict. I.